Predicting the time trend of first episodes of aggressive behaviors in pediatric psychiatric inpatient units. (August 2021) - Lin, Ping-I; Bonander, Carl; Harmeyer, Kathryn; Kennedy, Patrick; Sorter, Michael; Osborn, Alexander; Barzman, Drew
Abstract: The goal of the current study is to assess whether the scores of Brief Rating of Aggression by Children and Adolescents (BRACHA) at the emergency room (ER) can predict the aggressive incidents at pediatric psychiatric inpatient units. The study aims to identify predictors for two outcome measurements: 1) hazard rates for the first aggressive incident and 2) numbers of days between admission and the first aggressive incident, using the Cox regression model and Poisson regression model, respectively. The clinical records of a total of 5, 610 adolescents admitted into the pediatric psychiatric inpatient units of Cincinnati Children's Hospital Medical Center were extracted for the analysis. The aggressive incident was defined as a score >0 from any category of the Overt Aggression Scale (OAS) and the high-aggressive incident was defined as a score ≥ 2 from any category of the OAS. The results indicate that the BRACHA score was not associated with high-aggressive incidents (hazard ratio: 0.98, p  = 0.7543). Similarly, the BRACHA scores was only associated with the number of days from admission to the first aggressive incident (Poisson regression coefficient: 0.24, p  < 0.0001) but not the number of days from admission to the first high-aggressive incident (Poisson regression coefficient: 0.03, p  = 0.3994). Furthermore, the second peak of first aggressive incidents during the hospitalization highlights the importance of interventions at the end of the inpatient treatment course. To summarize, BRACHA scores based on initial assessments at the ER could correlate with first aggressive incidents, but not the first high-aggressive incidents.